Perfil de dispensação de antibacterianos e perfil microbiológico de hospitais de referência para tratamento de COVID-19 no Espírito Santo - Pereira, Maria Luiza Scardua (2021)
With the increase in the number of hospitalizations for COVID-19, a disease caused by the SARS-CoV-2 virus, we must adapt to this new reality. In addition to the suspension of surgeries and elective services, there was a change in the profile of patients who were treated at these hospitals. Consequently, there may be a change in their microbiological profile, which may put antibiotic therapy protocols into question. In addition, the need for mechanical problems, decreased immunity and long hospital stay may favor the emergence of bacterial infections secondary to COVID-19. Thus, the aim of the study is to assess the impact of the first year of the COVID-19 pandemic on the dispensing of antibacterial and the occurrence of priority bacterial pathogens for monitoring antimicrobial resistance in three reference hospitals (HDS, HJSN and HRAS) for the treatment of COVID-19 in Espírito Santo. The work in question is an ecological descriptive study of data generated two years before the pandemic (2018 and 2019) and in the first year of the pandemic by COVID-19 (2020), from the pharmacy and microbiology sector of the hospitals of origin. After approval by the Ethics and Research Committee of the Federal University of Espírito Santo (UFES) (protocol 4,374,111), data were generated through the hospital's MV2000i system and later spreadsheeted in Excel (Microsoft ® 365). For comparative analysis, microorganisms and antibacterial occurring in the three periods of the study were considered. We performed the Shapiro-Wilk normality test and the student t test for pairs. Decreased the decrease in the dispensing of antibacterial in two of the three hospitals studied in 2020, the first year of the COVID-19 pandemic; There was a significant increase in medications used to treat community-acquired bacterial pneumonia (azithromycin, ceftriaxone and polymyxin B); The frequency of Acinetobacter spp., Pseudomonas aeruginosa and Klebsiella pneumoniae resistant to carbapenems, also Enterococcus spp. vancomycin resistance increased in 2020 in the two hospitals analyzed; The occurrence of drug-resistant K. pneumoniae followed the evolution of the number of cases of COVID-19 in ES in the first year of the pandemic.